Psychological well-being of single working mothers: The influence of spiritual intelligence and social support - Rifayanti, Rina; Suhesty, Aulia; Wahyuni, Ridha; Pramesti, Shinta Aprillia; Wardani, Riska; Azmi, Siti Nur (Jurnal Ilmiah Psikologi Terapan, 2025)
The number of single mothers who must carry out dual roles as housewives and breadwinners is significant. This single-mother status means that dual roles must be fulfilled. This research aims to determine the influence of spiritual intelligence and social support on psychological well-being among single working mothers. The method used in this research is a quantitative approach with multiple linear regression analysis techniques. The sample in this study consisted of single mothers who worked, either due to divorce or widowhood, with a total of 105 respondents selected using purposive sampling. The research results showed that, simultaneously, spiritual intelligence and social support could influence the psychological well-being of single working mothers by 55.7%. Additionally, both spiritual intelligence and social support individually influence psychological well-being. This research supports the theory that psychological well-being is influenced by internal (spiritual intelligence) and external (social support) factors. These findings can serve as a basis for further research to develop intervention models aimed at improving the psychological well-being of single working mothers.